2011
DOI: 10.1007/s12011-011-9177-8
|View full text |Cite
|
Sign up to set email alerts
|

Correlations of Trace Element Levels in the Diet, Blood, Urine, and Feces in the Chinese Male

Abstract: In order to explore the associations between trace elements in dietary intake and the other three biological media (blood, urine, or feces) and inter-element interactions among the latter, we simultaneously collected 72-h diet duplicates, whole blood, and 72-h urine and feces from 120 free-living healthy males in China. Correlations among the toxic (cadmium [Cd], lead [Pb]), and nutritionally essential (zinc [Zn], copper [Cu], iron [Fe], manganese [Mn], selenium [Se], iodine [I]) elements were evaluated using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
17
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(22 citation statements)
references
References 44 publications
4
17
0
1
Order By: Relevance
“…A correlation of dietary Cd, as assessed with food frequency questionnaires, with Cd levels in blood and urine has been found in some studies but not in others (Julin et al, 2011;Wang et al, 2012;Ikeda et al, 2015;Vacchi-Suzzi et al, 2015;Wang et al, 2015). Factors explaining this low concordance in the present study may be an inadequate assessment of dietary intake owing to an imprecise estimate of Cd content in foodstuffs, the low gastrointestinal absorption of Cd, generally in the order of 5% in adults (Andersen et al, 1992), the influence of other dietary variables such as fiber and iron which may modify Cd intake and metabolism (Berglund et al, 1994;Akesson et al, 2002;Olsson et al, 2002;Julin et al, 2011), and particularly the limited sample size.…”
Section: Discussionmentioning
confidence: 94%
“…A correlation of dietary Cd, as assessed with food frequency questionnaires, with Cd levels in blood and urine has been found in some studies but not in others (Julin et al, 2011;Wang et al, 2012;Ikeda et al, 2015;Vacchi-Suzzi et al, 2015;Wang et al, 2015). Factors explaining this low concordance in the present study may be an inadequate assessment of dietary intake owing to an imprecise estimate of Cd content in foodstuffs, the low gastrointestinal absorption of Cd, generally in the order of 5% in adults (Andersen et al, 1992), the influence of other dietary variables such as fiber and iron which may modify Cd intake and metabolism (Berglund et al, 1994;Akesson et al, 2002;Olsson et al, 2002;Julin et al, 2011), and particularly the limited sample size.…”
Section: Discussionmentioning
confidence: 94%
“…Wang et al (2012) reported correlations among the toxic (Cd, Pb) and nutritionally essential (Zn, Cu, Fe, Mn, Se) elements in the blood, also urine and feces in the male. In the case of the toxic metals, a significant positive correlation was found for Cd–Pb in blood and a moderate correlation in urine.…”
Section: Resultsmentioning
confidence: 99%
“…One is instrumental analysis using inductively coupled plasma-mass spectrometry (ICP-MS) after alkali digestion. ICP-MS [18] has been gaining popularities in recent years as a tool to measure iodine in various biological materials including foods [19][20][21][22][23]. The other is FCT-based estimation.…”
Section: Introductionmentioning
confidence: 99%